Digital twins in sustainable transition: exploring the role of EU data governance - Garske, Beatrice; Holz, Wilmont; Ekardt, Felix (Frontiers in Research Metrics and Analytics, 2024)
Digital twins can accelerate sustainable development by leveraging big data and artificial intelligence to simulate state, reactions and potential developments of physical systems. In doing so, they can create a comprehensive basis for data-driven policy decisions. One of the purposes of digital twins is to facilitate the implementation of the EU's Green Dealin line with internationally binding climate and environmental targets. One prerequisite for the success of digital twins is a comprehensive, highquality database. This requires a suitable legal framework that ensures access to such data. The following article examines if the EU's strategies and legal acts on data governance are paving the way for digital twin projects which promote sustainability. Results show important starting points for open and fair data use within the growing field of EU digital law. However, there is still a lot of progress to be made to legally link the use of digital twins with binding sustainability objectives.